2023
DOI: 10.1186/s40793-023-00532-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct coral environments shape the dynamic of planktonic Vibrio spp.

Wenbin Zhao,
Xing Chen,
Ronghua Liu
et al.

Abstract: Background Coral reefs are one of the most biodiverse and productive ecosystems, providing habitat for a vast of species. Reef-building scleractinian corals with a symbiotic microbiome, including bacteria, archaea, viruses and eukaryotic microbes, are referred to coral holobionts. Among them, coral diseases, mainly caused by Vibrio spp., have significantly contributed to the loss of coral cover and diversity. Habitat filtering across the globe has led to a variety structure of marine bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…On the contrary, Daya Bay had the least abundance and diversity of bacteria, with 81 strains belonging to 20 species and 8 genera. The reason might be that the number and species of coral in the SSCS and DY may have significant differences, and it has been reported that bacteria usually show separated distributions in coral-rich (Xisha Islands) and coral-poor areas (Daya Bay) [ 58 ]. In addition, there are discrepancies in the related bacteria species among different coral species in the SCS, which may be related to the adaptation of coral to the marine environment with latitude variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Daya Bay had the least abundance and diversity of bacteria, with 81 strains belonging to 20 species and 8 genera. The reason might be that the number and species of coral in the SSCS and DY may have significant differences, and it has been reported that bacteria usually show separated distributions in coral-rich (Xisha Islands) and coral-poor areas (Daya Bay) [ 58 ]. In addition, there are discrepancies in the related bacteria species among different coral species in the SCS, which may be related to the adaptation of coral to the marine environment with latitude variation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Flammeovirga is a relatively new genus, and only seven valid species have been included in the NCBI database [ 65 ]. Thus, coral reefs may provide special environmental conditions for the survival of microorganisms, which are richer in organic matters than non-reef areas [ 58 ].…”
Section: Discussionmentioning
confidence: 99%